(untitled) (Research, Society and Development, 2023)
In the objective conditions of mercantile-capitalist society, the commodity form or interchangeability, becomes the social form of the social relations of production. In this sociability, “wealth [...] appears as an immense collection of goods”. In these circumstances, the central question of this research project is how the education complex, in the objective conditions of mercantile-capitalist society, assumes the form of merchandise. To deal with this issue, we chose as a general objective to explain, from the perspective of Marxian political economy, how the education complex takes the form of a commodity. And as specific objectives, describe the fundamental elements of mercantile-capitalist society: private and isolated producers, concrete and abstract work and the exchange process; demonstrate interchangeability as the social form of the social relations of production in mercantile-capitalist society; make explicit the constitutive elements of merchandise in the education complex: value, use value and exchange value, concrete and abstract work. To carry out our study, we will use the thought of Marx and interpretations. We will use onto-methodological assumptions in the development of bibliographical research from the perspective of historical-dialectical materialism.